An exploration of ethnomathematics at Sewu Temple in Yogyakarta - Sulistyowati, Dina; Khotimah, Rita Pramujiyanti (Jurnal Riset Pendidikan Matematika, 2022)
This study explores the elements of mathematics (geometry and arithmetic) in Sewu Temple. As the research is qualitatively discussed, ethnographic design is appropriately implemented with observation, interviews, and documentation for collecting data. The data analysis technique shares four steps; collecting, reducing, presenting, and drawing a conclusion"”the validity of the data using triangulation techniques. The results of this study indicate that there are mathematical elements in the shape of the building and the reliefs of Sewu Temple; flat shapes, spatial shapes, geometric transformations, and arithmetic sequences. The existing flat forms include; squares, rectangles, isosceles trapezoids, right trapezoids, circles, triangles, and octagons. Furthermore, blocks, tubes, and rectangular pyramids are included in existing shapes. The geometric transformations are in the form of reflection (mirror), translation (shift), and dilation (multiplication). The results of the ethnomathematical exploration at Sewu Temple can be used as instructional teaching for mathematics in schools, especially in geometry, geometric transformations, and arithmetic sequences.